Utilizing waste heat gasoline engine in the design and fabrication of a fin and tube evaporator for the Organic Rankine Cycle (ORC) - Awaludin Martin; Rudi Hartono; Reza Asrian (Universitas Mercu Buana, 2023)
The excessive consumption of fossil fuels is causing environmental problems, which can be addressed by utilizing renewable energy sources such as hydro energy, biomass, solar heat, geothermal, and waste heat. In particular, the exhaust gas from gasoline engines presents an opportunity for energy recovery, as only 25% of the energy is utilized while the remaining 75% is wasted. A fin and tube type evaporator was designed, manufactured, and tested to utilize this exhaust gas in an Organic Rankine Cycle (ORC) system. The evaporator was designed with an outer tube diameter of 9.525 mm and a total tube length of 41.4 m, featuring 90 tubes and 135 fins with a total area of 14,325 m2. It achieved an average effectiveness of 94.33%. The results showed that the waste heat from the exhaust gas of a gasoline engine could be used as a source of energy in an ORC system with an efficiency of 2.13%. It results in 7.02 kJ/s of energy absorbed by the evaporator and a net power generated of 0.15 kJ/s. This research demonstrates the potential for utilizing waste heat from gasoline engines as an energy source to generate electricity.